1990
DOI: 10.2527/1990.68113536x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods of selection for litter size in mice: I. Characterization of base population and development of methods.

Abstract: Studies on a base population of mice were used to establish an index of components of litter size and a physiological model for measuring uterine capacity to be used subsequently in a selection experiment evaluating alternative methods for practicing selection to increase litter size. Heritability estimates of litter size, ovulation rate and ova success (fraction of ova resulting in fully formed pups) were .18, .33 and .15, respectively. No significant genetic or phenotypic correlation was found between overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
39
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 0 publications
14
39
2
Order By: Relevance
“…Conversely, the value obtained for weight at puberty is larger than most literature estimates (Young et al, 1978;Hutchens et al, 1981 (Neal et al, 1989) and with estimates obtained in mice and rabbits (Clutter et al, 1990;Blasco et al, 1993b (Young et al, 1977), 50 days of gestation (Neal et al, 1989) or at birth (Young et al, 1978) is observed. This may be due to differences in the populations studied, but may also indicate that uterine competition tends to increase throughout gestation.…”
contrasting
confidence: 44%
“…Conversely, the value obtained for weight at puberty is larger than most literature estimates (Young et al, 1978;Hutchens et al, 1981 (Neal et al, 1989) and with estimates obtained in mice and rabbits (Clutter et al, 1990;Blasco et al, 1993b (Young et al, 1977), 50 days of gestation (Neal et al, 1989) or at birth (Young et al, 1978) is observed. This may be due to differences in the populations studied, but may also indicate that uterine competition tends to increase throughout gestation.…”
contrasting
confidence: 44%
“…Estimations of base population parameters were reported by Clutter et al (1990). The population was partitioned into three replicates and then into four lines within each replicate; line in this paper will refer to a replicatecriterion population.…”
Section: Generation Of Lines and General Proceduresmentioning
confidence: 99%
“…They concluded that selection for litter size in these gilts would be essentially independent of ovulation rate and, thus, would improve genetic merit for uterine capacity. Clutter et al ( 1990) reported phenotypic correlations between numbers of corpora lutea and fetuses of .57 on the left and .70 on the right side in intact females from the base generation of the present population. Clearly, unilateral ovariectomy has resulted in a greater independence between ovulation rate and number of fetuses, but the correlation is still greater than zero.…”
mentioning
confidence: 99%
“…1994. 72:577-583 explored by Clutter et al (1990), Gion et al (19901, and Kirby and Nielsen (1993). The purpose of the present study was to evaluate responses in uterine capacity and ovulation rate of mice due to selection for either uterine capacity, litter size, or an index of ovulation rate and ova success.…”
Section: Introductionmentioning
confidence: 99%